Microstructural studies of Cu-Al Intermetallic Compound at Thermosonic Wire Bonding Interface - Thangaraj, Joseph Sahaya Anand; Chua, Kok Yau; Abd Rashid, Mohd Warikh; Hng, May Ting; Lee, Cher Chia (2012)
Cu-Al intermetallic compound (IMC) in Cu wire-Al bond pad bonding interface has been an area of interest for researchers. In this paper, characterization of IMC at bonding interface of annealed diode micro-chip has been performed using Scanning Electron Microscope (SEM), Transmission Electron Microscope (TEM), Energy Dispersive X-ray (EDX) as well as less commonly used X-ray Diffraction (XRD). Combination of these techniques offers overall picture of the micro-structure and crystallography of the IMC at the bonding interface. SEM imaging and line scan EDX reveal the interdiffusion zone of Cu-Al. TEM imaging with EDX line scan and phase diagram deduce the phase of IMC present at the interdiffusion zones. Slow XRD scan of powder sample detects only the CuAl phase in the sample which implies that this phase is dominant in the sample.